Wogonin suppresses proliferation and invasion of skin epithelioid carcinoma cells through Notch1 - Xin, Nai-Jun; Han, Mei; Gao, Cong; Fan, Tao-Tao; Shi, Wen (Cellular and Molecular Biology, 2020)
The current study was carried out to investigate the role of wogonin in proliferation and invasion of skin epithelioid carcinoma cells as well as its underlying mechanisms. For this purpose, skin epithelioid carcinoma cells were treated with 0, 5, 10 and 20Î¼mol/L wogonin for 24, 48, 72 hours. Cell proliferation was evaluated by an MTT assay. Cell invasion was assessed by the Transwell invasion assay. The Notch1 level was analyzed by RT-qPCR for mRNA and by Western blot for protein. Results showed that wogonin inhibited the proliferation and invasion of skin epithelioid carcinoma cells in a dose-dependent manner. Wogonin treatment significantly decreased the mRNA and protein levels of Notch1. Moreover, the inhibition of cell proliferation and invasion ability by wogonin treatment was dramatically attenuated after co-treatment with 20 ng/mL doxycycline, a specific Notch1 activator. In conclusion, wogonin may inhibit skin epithelioid carcinoma cell proliferation and invasion at least partially by repressing the Notch1 gene expression.